The association between passive social network usage and depression/negative emotions with envy as a mediator - Wen Cheng; Duc Nhan Nguyen; Pham Ngoc Thien Nguyen (Scientific Reports, 2023)
Abstract This study aimed to investigate the relationships between passive social network usage (PSNU) and depression/negative emotions over time with the mediating role of envy among Vietnamese adolescents. First, it revealed that PSNU had a simultaneous effect on depression/negative emotions as well as at different time points, indicating that social network site behaviors can predict psychological states over time (explained by the social comparison theory). Second, the autoregressive effect also confirmed a potential reciprocal relationship between PSNU and depression, whereas PSNU appeared to have an impact on negative emotions but not the other way around. Specifically, depression at Time 1 was positively associated with PSNU at Time 2, whereas negative emotions did not exhibit a similar pattern (explained by the cognitive dissonance theory). The different associations were interpreted as depression having cognitive elements, while negative emotions were thought to be purely emotional states. The results demonstrated that behavior may potentially have a long-lasting effect on mental health (both negative emotions and depression), while it was depression, rather than negative emotions, that had a long-term effect on behaviors. Third, envy played a mediating role that connected the changes of PSNU and depression/negative emotions. The implications and limitations of these findings are discussed.